THE ROLE OF TRANSPARENCY AND RELIABILITY IN FINANCIAL STATEMENT: REFERENCE TO INDIAN CORPORATE SECTOR - Matkar, Anil; Ranjan, Prof. Satya S. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The role of transparency and reliability in financial statements is necessary to not only for the investors, but also for the business and the accounting corporate. It is regular process of Financial Accounting for identifying, posting, analysing and communicating economic information to the stakeholders to their management decision The purpose of this research is to find the existence of reliability and transparency in the financial statement, for the benefit of investors and scholars. The scope of the study is to find the relationship of accounting standards, corporate governance, external controls, internal controls, and ethical practices with the financial statements, based on the auditors and management views the corporate sector in India. The existence of transparency and reliability in financial statements was related with accounting standards, ethical practices, internal controls, external controls, and corporate governance. The outcome will be supported by many tests through SPSS statistic software.